Unexplained Graft Dysfunction after Heart Transplantation—Role of Novel Molecular Expression Test Score and QTc-Interval: A Case Report. (22nd June 2010) - Shahzad, Khurram; Cadeiras, Martin; Arai, Kotaro; Abramov, Dmitry; Burke, Elizabeth; Deng, Mario C.
Abstract : In the current era of immunosuppressive medications there is increased observed incidence of graft dysfunction in the absence of known histological criteria of rejection after heart transplantation. A noninvasive molecular expression diagnostic test was developed and validated to rule out histological acute cellular rejection. In this paper we present for the first time, longitudinal pattern of changes in this novel diagnostic test score along with QTc-interval in a patient who was admitted with unexplained graft dysfunction. Patient presented with graft failure with negative findings on all known criteria of rejection including acute cellular rejection, antibody mediated rejection and cardiac allograft vasculopathy. The molecular expression test score showed gradual increase and QTc-interval showed gradual prolongation with the gradual decline in graft function. This paper exemplifies that in patients presenting with unexplained graft dysfunction, GEP test score and QTc-interval correlate with the changes in the graft function.